What Is That? Innumerable Mysterious Densities Identified on Abdominal Imaging. Issue 2 (February 2020) - Kaiser, Nicole; Blackford, Martha G.
Abstract : Abstract: Radiopaque densities can be observed on imaging after the ingestion of either foreign bodies or some medications. Our case report discusses an 11-year-old boy with autism spectrum disorder and attention deficient disorder who presented to the emergency department because of concerns for constipation and dehydration. Incidentally, an abdominal x-ray showed numerous radiopaque densities throughout his intestines in addition to his constipation. He was admitted, and his home regimen was reviewed to attempt to identify a potential source for these radiopaque densities. This case presented an interesting teaching opportunity in the identification of the radiopaque densities and review of pharmacokinetics.